2019
DOI: 10.7759/cureus.4420
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension Masking as Obstructive Hydrocephalus: A Case Report

Abstract: Idiopathic intracranial hypertension (IIH) is a poorly understood phenomenon and its presentation can both mimic and co-exist with other intra-cranial processes. Accurate diagnosis is imperative as ongoing advancements in treatment can yield dramatic positive results. Here we present the case of an individual with signs and symptoms of obstructive hydrocephalus who was ultimately found to have IIH secondary to venous sinus stenosis. After correction of the venous sinus stenosis, resolution in the patient's sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Following an extensive systematic review, our patient's gradient pressure surpasses all others documented in the literature (Table). 3-52 According to our systematic review, the highest recorded gradient pressure was 67 mm Hg reported by Tschoe et al 36 who highlighted the impact of changes in mean arterial pressure and end-tidal carbon dioxide on venous sinus pressures in patients with IIH undergoing venous sinus stenting. Moreover, Ahmed et al reviewed clinical, venographic, and intracranial pressure data before and after stent placement in transverse sinus stenosis in 52 patients with IIH; the highest pressure gradient they reported was 41 mm Hg.…”
Section: Discussionmentioning
confidence: 82%
“…Following an extensive systematic review, our patient's gradient pressure surpasses all others documented in the literature (Table). 3-52 According to our systematic review, the highest recorded gradient pressure was 67 mm Hg reported by Tschoe et al 36 who highlighted the impact of changes in mean arterial pressure and end-tidal carbon dioxide on venous sinus pressures in patients with IIH undergoing venous sinus stenting. Moreover, Ahmed et al reviewed clinical, venographic, and intracranial pressure data before and after stent placement in transverse sinus stenosis in 52 patients with IIH; the highest pressure gradient they reported was 41 mm Hg.…”
Section: Discussionmentioning
confidence: 82%
“…We found 42 articles with 105 cases: 48 pediatric and 57 adult (71112), Table 4. The distribution was as follows: hematological diseases (N = 16) (9093,95104,106,107), rheumatologic diseases (N = 7): Behçet’s disease and systemic lupus erythematosus (SLE) (71,72,83,94,105,108,109), different genetic diseases (N = 5) (73,74,…”
Section: Resultsmentioning
confidence: 99%